INFLUENCE OF LEVERAGE, FIRM SIZE, AND SALES GROWTH ON FINANCIAL DISTRESS - Ingkak Chintya Wangsih; Devia Rahma Yanti; Yohana Yohana; Nawang Kalbuana; Catra Indra Cahyadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to find out either the partial or simultaneous effect of leverage, firm size, and sales growth on financial distress. The population in this study are retail trade sub-sector companies listed in Indonesia Stock Exchange (IDX) period 2016-2020 with total 27 companies. The sample’s determination in this study used purposive sampling technique, so that obtained 17 companies. The data analysis method used logistic regression analysis and the data processing used SPSS. Testing the influence of variables on the partial test (wald test) shows the results that leverage has a significance value of 0.041 (sig < 0.05) and a positive B regression coefficient (2.303) then Ho is rejected and Ha is accepted, which means partially leverage has significant positive effect on financial distress. Firm size has a significance value of 0,027 (sig < 0,05) and a negative B regression coefficient (-0,527) then Ho is rejected and Ha is accepted, which means partially firm size has significant negative effect on financial distress. Sales growth has a significance value of 0,655 (sig > 0,05) then Ho is accepted and Ha is rejected, which means partially sales growth has no significant effect on financial distress. Testing the influence of variables on the simultaneously test (omnibus test) shows the results that simultaneously the leverage, firm size, and sales growth has effect on financial distress.